Neural Circuits Revealed - Mariano Soiza Reilly (Frontiers Research Topics, 2015)
Deciphering anatomical and functional maps in the nervous system is a main challenge for both clinical and basic neuroscience. Modern approaches to mark and manipulate neurons are bringing us closer than ever to better understand nervous system wiring diagrams. Here we present both original research and review material on current work in this area. Together, this eBook aims to provide a comprehensive snapshot of some of the tools and technologies currently available to investigate brain wiring and function, as well as discuss ongoing challenges the field will be confronted with in the future.